







CTK Exchange

JJ
guest

Jan2407, 05:01 AM (EST) 

2. "RE: A difficult one:"
In response to message #1

ln(3^x) = ln(4^y) = ln(12^z) x*ln(3) = y*ln(4) = z*ln(12) y = z*ln(12)/ln(4) x = z*ln(12)/ln(3) (1/x)+(1/y) = (ln(3)/(z*ln(12))+(ln(4)/(z*ln(12)) (1/x)+(1/y) = (ln(3)+ln(4)/(z*ln(12) 1/x)+(1/y) = ln(12)/(z*ln(12) 1/x)+(1/y) = 1/z


Alert  IP 
Printerfriendly page 
Reply 
Reply With Quote  Top 



You may be curious to have a look at the old CTK Exchange archive. Please do not post there.
Copyright © 19962018 Alexander Bogomolny

